RUBE2D: a web-based customisable 2D modelling and simulation system. (2nd June 2005) - Shim, Hyunju; Fishwick, Paul A.
Modelling systems tend to involve the use of fixed visual icons for representing entities such as state, event, function and activity. We have developed a web-based modelling and simulation framework that is constructed on top of an open source diagram editor, thus making it possible to build many model types, each with arbitrary visual objects. We can also combine the system being modelled, in conjunction with the model yielding an interactive diagram suitable for web deployment. We provide a dynamic multimodel of four-stroke engine behaviour, and a diagram of the engine, to demonstrate the customisation attributes of RUBE2D. The customisation procedure involves some initial time overhead, but this can minimised with the ability to create model type icon libraries.